Keragaman Ekspresi Lokus Gen Kucing Peranakan Anggora Hasil Perkawinan Silang Alami - Nofisulastri Nofisulastri; Supriadi Supriadi (Bioscientist : Jurnal Ilmiah Biologi, 2021)
This research is a follow-up study by presenting the extent of the expression pattern and the presence of each allele locus that marks the color pattern on the cat's body, to add a reference in making it easier for the cat breeder community to form relatively uniform color patterns in certain crossing periods. This research is a descriptive exploratory case study presented qualitatively. Cat samples were screened based on a minimum age of 1 year, and 30 individuals were collected by road sampling. Observation of sample morphology based on mating pathway, recording of morphological characters (body color, color pattern, and tail length). Data were analyzed using allele frequency calculations for genes (dominant and recessive relationship) and concluded qualitatively. The frequency of the presence of gene loci and their alleles was found as many as 8 gene loci, namely: w-W; A A; B-b; C_cb_cs_ca_c; Ta_T_tb; D-d; s-S; OO-oo-Oo; and M-m, and no D-d and I-i gene loci were found. It was concluded that the observed gene locus expression of the Angora crossbreed cat had a variety of random allele frequencies, and did not indicate any particular allele dominance.